Microevolution in Trifolium L. Sect. Stenostoma M. B. I. biometry of spontaneous and cultivated Trifolium pannonicum Jacq. - Attila T. SZABO (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 1987)
The variability of spontaneous and cultivated (selected) Trifolium pannonicum Jacq. (2n=16x - 22x) has been studied by using herbal specimens, samples collected from spontaneous populations, cultivated ones and selected elite plants. The biometry of economically and/or taxonomically important characters have been performed, results tabulated and statistical indicators - mean, standard deviation, coefficient of variation - calculated. These values indicate differences between the eastern and western accessions with regard to peduncle length, petiole length, leaf size, hairiness etc. Based on these differences a new taxon var. moldavicum var. nova has been proposed. Cultivation revealed that the diploid T. ochroleucon Huds. is a short living plant (1-2 years), but polyploid T. pannonicum persisted up to 10 years or more. Natural selection for disease resistance and persistence did not narrowed sharply the variability of the selected elites. In elite plants the coefficient of variability was especially high for underground organs (number of lateral roots, root noduls for unit root length etc.), characters positively correlated with yield components. Problems relating to taxonomy, evolution, domestication and use of the species are also briefly discussed.